Scary and nasty beasts: Self-reported fear and disgust of common phobic animals - Polák, Jakub; Rádlová, Silvie; Janovcová, Markéta; Flegr, Jaroslav; Landová, Eva; Frynta, Daniel (British journal of psychology (London, England, 2020)
Animal phobias are one of the most prevalent mental disorders. We analysed how fear and disgust, two emotions involved in their onset and maintenance, are elicited by common phobic animals. In an online survey, the subjects rated 25 animal images according to elicited fear and disgust. Additionally, they completed four psychometrics, the Fear Survey Schedule II (FSS), Disgust Scale - Revised (DS-R), Snake Questionnaire (SNAQ), and Spider Questionnaire (SPQ). Based on a redundancy analysis, fear and disgust image ratings could be described by two axes, one reflecting a general negative perception of animals associated with higher FSS and DS-R scores and the second one describing a specific aversion to snakes and spiders associated with higher SNAQ and SPQ scores. The animals can be separated into five distinct clusters: (1) non-slimy invertebrates; (2) snakes; (3) mice, rats, and bats; (4) human endo- and exoparasites (intestinal helminths and louse); and (5) farm/pet animals. However, only snakes, spiders, and parasites evoke intense fear and disgust in the non-clinical population. In conclusion, rating animal images according to fear and disgust can be an alternative and reliable method to standard scales. Moreover, tendencies to overgeneralize irrational fears onto other harmless species from the same category can be used for quick animal phobia detection.
Keywords: dospělí; Animals; Phobic Disorders; Emotions; průzkumy a dotazníky; Female; Psychometrics; snakes; psychometrie; Adult; ženské pohlaví; factor analysis; Surveys and Questionnaires; emoce; lidé; Self Report; Affect; afekt; Fear; strach; odpor; spiders; Male; fobie; zvířata; mužské pohlaví; zpráva o sobě; preparedness theory; disease-avoidance model; animal phobia; Disgust; Humans